Execution of The Right to be Forgotten in Indonesia: The Urgency of the Requirements for the Determination and Establishment of the Assessment Body - Sugeng Sulistyo, Trisoko; Johan Utama, Yos; Putrijanti, Aju (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Right to be Forgotten has been recognized in the Information and Electronic Transactions Law (ITE) and the Personal Data Protection Law (PDP), but has not been regulated in detail. The ITE Law and the PDP Law do include provisions on the right to be forgotten, but there is no specific explanation of the conditions that must be met to establish what rights can be removed as part of the Right to Be Forgotten. In addition, there is no special assessment body tasked with determining and assessing these conditions. This ambiguity causes the implementation of the Right to be Forgotten to be hampered in Indonesia. This journal aims to provide recommendations for policymakers to improve related regulations so that the implementation of the Right to be Forgotten can run effectively in Indonesia so that it has benefits for law enforcement in Indonesia. The method used in this journal is normative juridical research with a statute approach. The results of the study show that in order for the implementation of The Right to be Forgotten to be more effective, it is necessary to prepare clearer determination requirements and the establishment of an independent assessment body that can handle applications fairly and transparently.